Trap inlaid cationic hybrid composite material for efficient segregation of toxic chemicals from water - Fajal, Sahel; Mandal, Writakshi; Mollick, Samraj; More, Yogeshwer D.; Torris, Arun; Saurabh, Satyam; Shirolkar, Mandar M.; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2022)
Metal-based oxoanions are potentially toxic pollutants that can cause serious water pollution. Therefore, the segregation of such species has recently received significant research attention. Even though several adsorbents have been employed for effective management of chemicals, their limited microporous nature along with non-monolithic applicability has thwarted their large-scale real-time application. Herein, we developed a unique anion exchangeable hybrid composite aerogel material (IPcomp-6), integrating a stable cationic metal-organic polyhedron with a hierarchically porous metal-organic gel. The composite scavenger demonstrated a highly selective and very fast segregation efficiency for various hazardous oxoanions such as, HAsO42-, SeO42-, ReO4-, CrO42-, MnO4-, in water, in the presence of 100-fold excess of other coexisting anions. The material was able to selectively eliminate trace HAsO42- even at low concentration to well below the As-v limit in drinking water defined by WHO.
Keywords: Aerogel; Chemical Separation; Hybrid composite; Metal-Organic Gel; Metal-Organic Polyhedra

Trap inlaid cationic hybrid composite material for efficient segregation of toxic chemicals from water (vol 61, e202203385, 2022) - Fajal, Sahel; Mandal, Writakshi; Mollick, Samraj; More, Yogeshwer D.; Torris, Arun; Saurabh, Satyam; Shirolkar, Mandar M.; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2022)

Nanotrap infused ultrathin hybrid composite material for rapid and highly selective entrapment of 99TcO4- - Mandal, Writakshi; Fajal, Sahel; Majumder, Dipanjan; Sengupta, Arijit; Let, Sumanta; Urkude, Rajashri R.; Shirolkar, Mandar M.; Torris, Arun; Ghosh, Sujit K. (CHEMICAL SCIENCE, 2024)
Keywords: Adsorption; CAPTURE; EFFICIENT; Metal-organic framework; Removal; TECHNETIUM

Ultralight crystalline hybrid composite material for highly efficient sequestration of radioiodine - Fajal, Sahel; Mandal, Writakshi; Torris, Arun; Majumder, Dipanjan; Let, Sumanta; Sen, Arunabha; Kanheerampockil, Fayis; Shirolkar, Mandar M.; Ghosh, Sujit K. (Nature Communications, 2024)
Considering the importance of sustainable nuclear energy, effective management of radioactive nuclear waste, such as sequestration of radioiodine has inflicted a significant research attention in recent years. Despite the fact that materials have been reported for the adsorption of iodine, development of effective adsorbent with significantly improved segregation properties for widespread practical applications still remain exceedingly difficult due to lack of proper design strategies. Herein, utilizing unique hybridization synthetic strategy, a composite crystalline aerogel material has been fabricated by covalent stepping of an amino-functionalized stable cationic discrete metal-organic polyhedra with dual-pore containing imine-functionalized covalent organic framework. The ultralight hybrid composite exhibits large surface area with hierarchical macro-micro porosity and multifunctional binding sites, which collectively interact with iodine. The developed nano-adsorbent demonstrate ultrahigh vapor and aqueous-phase iodine adsorption capacities of 9.98 g.g-1 and 4.74 g.g-1, respectively, in static conditions with fast adsorption kinetics, high retention efficiency, reusability and recovery. The development of effective adsorbents of radioiodine nuclear waste remains difficult due to the lack of proper material design strategies. Here the authors report an ultralight hierarchically porous crystalline multifunctional hybrid nanocomposite for ultrafast entrapment of iodine and polyiodide species under both static and dynamic condition.

Nano-springe enriched hierarchical porous MOP/COF hybrid aerogel: efficient recovery of gold from electronic waste - Majumder, Dipanjan; Fajal, Sahel; Shirolkar, Mandar M.; Torris, Arun; Banyla, Yashasvi; Biswas, Kishalay; Rasaily, Sagarmani; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2025)
Extraction of gold from secondary resources such as electronic waste (e-waste) has become crucial in recent times to compensate for the gradual scarcity of the noble metal in natural mines. However, designing and synthesizing a suitable material for highly efficient gold recovery is still a great challenge. Herein, we have strategically designed rapid fabrication of an ionic crystalline hybrid aerogel by covalent threading of an amino-functionalized metal-organic polyhedra with an imine-linked chemically stable covalent organic framework at ambient condition. The hierarchically porous ultra-light aerogel featuring imine-rich backbone, high surface area, and cationic sites have shown fast removal, high uptake capacity (2349 mg/g), and excellent selectivity towards gold sequestration. Besides, the aerogel can extract ultra-trace gold-ions from different terrestrial water bodies, aiming towards safe drinking water. This study demonstrates the great potential of the composite materials based on a novel approach to designing a hybrid porous material for efficient gold recovery from complex water matrices.
Keywords: Aerogel; COF; E-waste; Gold; MOP